BORDER REGIONS AS THE TOURIST DESTINATION - Majstorović, Vukica; Stankov, Uglješa; Stojanov, Sanja (International Journal of Economic Practice and Policy, 2013)
Tourism, as a global phenomenon, has found its place in every corner of the world. During a certain period of time, the tourism market has become saturated by mass tourism causing the creation of new attractive destinations for tourists. Thus, some of the border areas in the world attract and keep passers-by while transforming into the  new tourist destinations. In this paper, it is possible to see relations and interconnections between tourism and international boundaries. Tourism in border regions has an opportunity to activate these areas that are often neglected by the state. Some European countries have taken advantage of this opportunity and they improved their tourism industry by developing their border regions. This kind of tourism development can be applied in Serbia and, in that way, activate the border areas of our country. However, in order to develop tourism in these areas, it is necessary to have an adequate international cooperation between two or more states. This can be achieved by various instruments of cross-border cooperation in tourism through the engagement of neighbouring countries in joint plans and cooperation.
Keywords: tourism; borders; tourist destinations; international boundaries; border regions; international cooperation; cross-border cooperation